Feasibility of a home-based computerized cognitive training for pediatric patients with congenital or acquired brain damage: An explorative study. - Claudia Corti; Geraldina Poggi; Romina Romaniello; Sandra Strazzer; Cosimo Urgesi; Renato Borgatti; Alessandra Bardoni (PLoS ONE, 2018)
Objectives Pediatric brain damage is associated with various cognitive deficits. Cognitive rehabilitation may prevent and reduce cognitive impairment. In recent years, home-based computerized cognitive training (CCT) has been introduced in clinical practice to increase treatment opportunities for patients (telerehabilitation). However, limited research has been conducted thus far on investigating the effects of remote CCT for the juvenile population in contexts other than English-speaking countries. The aim of the present study was to investigate the feasibility of a home-based CCT in a group of Italian adolescents with brain damage. A commercially available CCT (Lumosity) developed in the English language was used due to the lack of telerehabilitation programs in the Italian language that allow stimulation of multiple cognitive domains and, at the same time, remote automatic collection of data. Thus, this investigation provides information on the possibility of introducing CCT programs available in foreign languages in countries with limited investment in the telerehabilitation field. Methods 32 adolescents aged 11-16 with a diagnosis of congenital or acquired (either traumatic or non-traumatic) brain damage participated in the study. They received 40 training sessions (5 days/week for 8 weeks). Before starting the training program, they received face-to-face demonstration of training exercises and written instructions in their mother tongue. The feasibility of both training and study design and procedures was assessed through 9 criteria taken from extant literature. Results All 9 feasibility criteria were met. 31 out of the 32 participants demonstrated adherence to the training program. 94.2% of training sessions were completed in the recommended timeframe. No significant technical issue was found. Conclusions Telerehabilitation seems to be a feasible practice for adolescents with brain damage. A training program developed in a foreign language can be used to counter the unavailability of programs in patients' mother tongue. Trial registration The trial is registered with the ISRCTN registry with study ID ISRCTN59250807.